Compliance with Infection Prevention and Control Standard Precautions among Physiotherapists in Regional Referral Hospitals in Dar es Salaam, Tanzania (Tanzania Medical Journal, 2025)
BackgroundThe practice of physiotherapy entails physical contact with clients, thus posing a risk for the practitioner and client to transmit infectious diseases to other clients and health workers. Infection prevention and control (IPC) is generally recognized as a vital component of comprehensive methods for patient and health provider safety, quality improvement and improved health outcomes.ObjectiveThis study aimed to assess compliance to IPC standard precautions and associated factors among physiotherapists at selected District and Regional Referral Hospitals in Dar es Salaam, Tanzania.MethodsA cross-sectional study using a qualitative approach was conducted. Participatory observation and in-depth interviews were used to collect data from three Regional Referral Hospitals and three District Hospitals in Dar es Salaam. Purposive sampling was used to select study participants. The in-depth interviews were digitally-recorded, transcribed verbatim, analyzed and subjected to a thematic analysis approach. ResultsCompliance to IPC standard precautions was assessed based on the 3 major categories, namely, regular environmental cleanliness; hand hygiene and decontamination of reusable equipment. Regular environmental cleanliness and decontamination of reusable equipment compliance was poor in district hospitals while hand hygiene compliance was moderate in both district and regional hospitals. Individual factors that influenced IPC standards precaution compliance were perceived benefits for preventing infections which have positive impacts on IPC. Behaviour factors related to IPC standard precaution practices were attitude and fear of contracting infection, which increased compliance with IPC. The study findings further revealed that work-related factors which were lack of training, lack of motivation, and poor working environments contributed to poor IPC compliance among physiotherapists. The study findings also revealed that a higher number of patients and shortage of staff led to an increase in workload, thus contributing to non-compliance with standard precautions; while supportive supervision increased compliance among physiotherapists.ConclusionPhysiotherapy clinic infrastructures should be improved to meet the standard requirements of the treatment room. Furthermore, in-service education on the importance of adhering to IPC among physiotherapists should be offered continuously.